Implementación de la contabilidad a la empresa “MASTER PC” YANTZAZA en el periodo octubre-diciembre 2024 - Villa Cobos, Jerson Ramiro (2025)
The present Curricular Integration Project, titled "Implementation of Accounting in the Company 'MASTER PC' YANTZAZA during the Period October-December 2024", by Ms. Danna Marieta García Macanchi, was developed with the aim of providing the company's manager with insights into its economic and financial situation. It highlights the importance of accounting implementation, which enables the assessment of whether the company is generating profits or losses, identifying outstanding debts or pending obligations from clients or suppliers, and ensuring proper control of each account to support informed decision-making by the manager. To achieve the objectives set in this study, a chart of accounts and an accounting manual were designed based on the company's needs, facilitating the chronological recording of daily transactions. Additionally, auxiliary formats were created to support the accounting process, including Payroll, Accounts Receivable, Accounts Payable, and Depreciation ledgers. An initial inventory was then conducted through a physical verification of all assets, liabilities, and obligations, leading to the preparation of the Initial Statement of Financial Position. The source documents were systematically classified, and an operations memorandum was prepared, followed by the general journal, where transactions were recorded chronologically. For inventory control, the Multiple Account System was applied. Using the collected information, the general ledger, trial balance, worksheet, and financial statements were prepared, which allowed for an assessment of the company’s economic and financial situation. The accounting process carried out in this commercial enterprise yielded the following financial results: Total Assets of $90,067.61, Total Liabilities of $15,689.97, and Equity of $74,377.64. Likewise, the Income Statement reported a net profit of $2,507.17. The Statement of Cash Flows incorporated operating and financing activities. This financial information is crucial for the business owner, as it serves as a basis for making informed decisions to promote the company's economic growth.